2013
DOI: 10.1371/journal.pone.0075342
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Human Obesity Reveals the Epigenetic Factor HDAC4 as a Potential Target for Obesity

Abstract: Sedentary lifestyle and excessive energy intake are prominent contributors to obesity; a major risk factors for the development of insulin resistance, type 2 diabetes and cardiovascular diseases. Elucidating the molecular mechanisms underlying these chronic conditions is of relevant importance as it might lead to the identification of novel anti-obesity targets. The purpose of the current study is to investigate differentially expressed proteins between lean and obese subjects through a shot-gun quantitative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 66 publications
7
62
0
2
Order By: Relevance
“…The finding that a homozygous form of the SDF-1 3′A genotype is more frequent in T2D patients with proliferative retinopathy by Djuric [61]. Due to the fact that reports exist to show that this genetic variation increases the CXCL12 protein expression, this may meant that some of circulatory CXCL12 is secreted by PBMCS as the main source of this chemokine which was previously supported by several lines of evidences [62,63].…”
Section: The Cxcl12 Genetic Variation In T2dmentioning
confidence: 79%
“…The finding that a homozygous form of the SDF-1 3′A genotype is more frequent in T2D patients with proliferative retinopathy by Djuric [61]. Due to the fact that reports exist to show that this genetic variation increases the CXCL12 protein expression, this may meant that some of circulatory CXCL12 is secreted by PBMCS as the main source of this chemokine which was previously supported by several lines of evidences [62,63].…”
Section: The Cxcl12 Genetic Variation In T2dmentioning
confidence: 79%
“…The investigators found that among obese patients, there were increases in proinflammatory signals such as thrombospondin-1, a glycoprotein with proinflammatory and antiangiogenic properties. 127 On the other hand, histone deacetylase 4, an epigenetic antiinflammatory regulatory protein, was downregulated among obese patients. Intriguingly, these abnormal protein profiles, although suggesting an overactive inflammatory response, could be significantly reversed by exercise.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 99%
“…Sixteen-week old wild type (WT) and the leptin-deficient ob/ob mice, a genetic model of obesity that becomes overweight due to hyperphagia, were studied for their hepatic lipidomic profiles using non-targeted analysis via ultra-performance liquid chromatography (UPLC) coupled to quadrupole mass spectrometry (MS). The obese mice had an increased level of TAG and DAG lipid species in the liver as well as diacylphosphoglycerols and ceramide species, while there was a decrease in the sphingomyelins [50]. Using high-fat feeding to induce obesity, Turner et al performed a tissue lipid profiling study over a course of time of the high-fat dietary intervention [51].…”
Section: Lipidomic Analysis In Tissues From Rodentsmentioning
confidence: 99%